1994
DOI: 10.1007/bf02888848
|View full text |Cite
|
Sign up to set email alerts
|

Lipase from a Brazilian strain ofPenicillium citrinum

Abstract: A lipases (glycerol ester hydrolases E. C. 3.1.1.3) from a brazilian strain of Penicillium citrinum has been investigated. When the microorganism was cultured in the simple medium (1.0% olive oil and 0.5% yeast extract), using olive oil in as carbon source in the inocula, the enzyme extracted showed maximum activity (409 IU/mL). In addition, decrease of yeast extract concentration also reduces the lipase activity. Nevertheless, when yeast extract was replaced by ammonium sulfate, no activity was detected. Puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 16 publications
3
29
0
1
Order By: Relevance
“…This finding was in agreement with that of Al-Saleh and Zahran who showed that enzyme was produced in the absence of organic nitrogen by Pseudomonas flourescens 21 . In a similar study, Pimentel et al recorded that a Brazilian strain of Penicillium citrinum produced a maximal lipase activity of 409 IU/mL in a medium that contained yeast extract 0.5 as the nitrogen source and further decrease in yeast extract concentration reduced the attainable lipase activity also 22 .…”
Section: Resultsmentioning
confidence: 86%
“…This finding was in agreement with that of Al-Saleh and Zahran who showed that enzyme was produced in the absence of organic nitrogen by Pseudomonas flourescens 21 . In a similar study, Pimentel et al recorded that a Brazilian strain of Penicillium citrinum produced a maximal lipase activity of 409 IU/mL in a medium that contained yeast extract 0.5 as the nitrogen source and further decrease in yeast extract concentration reduced the attainable lipase activity also 22 .…”
Section: Resultsmentioning
confidence: 86%
“…According to the work reported by Markossian et al (2000), B. thermoleovoraus showed maximum activity when yeast extract is used as nitrogen source. If the yeast extract is replaced by ammonium sulphate, no activity will be observed (Pimentel et al, 1994). Vmax and Km of PCSIRNL-39 lipase were measured to be 101 µmol/min/mL and 7.61 mg, whereas Vasiee et al (2016) reported Vmax and Km value of 0.367 μM/min/mL and 5.3 mM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The buffers used were citrate-phosphate (pH 5.0 -5.7, 0.1M), phosphate (pH 6.0 -8.0, 0.1M), and Tris-HCl (pH 7.2 -9.0, 0.2M) Pimentel et al (14).…”
Section: Effect Of Ph On Protease Activitymentioning
confidence: 99%